2012
DOI: 10.13005/msri/090113
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Approach for Optimization of Sinker Electric Discharge Machine Process Parameters on AISI 4140 Alloy Steel

Abstract: The purpose of this paper is to determine the optimal factors of the electro-discharge machining (EDM) process investigate feasibility of design of experiment techniques. The work pieces used were rectangular plates of AISI 4140 grade steel alloy. The study of optimized settings of key machining factors like pulse on time, gap voltage, flushing pressure,input current and duty cycle on the material removal,surface roughness is been carried out using central composite design. The output responses measured were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…R-sq. was obtained to be within the limit [39][40][41]. The close relation of the R-square values signifies the model is appropriate for predicting the future outcomes of MRR [42].…”
Section: Analysis Of Mrrmentioning
confidence: 63%
“…R-sq. was obtained to be within the limit [39][40][41]. The close relation of the R-square values signifies the model is appropriate for predicting the future outcomes of MRR [42].…”
Section: Analysis Of Mrrmentioning
confidence: 63%
“…Powders with specific materials are added to the dielectric fluid to improve its breakdown characteristic. The series discharges caused by the powders enlarge the sparking gap, which can facilitate the removal of the debris and stable machining process [142][143][144]. The added powder would be energised and move in a zigzag fashion during the pulse-on time.…”
Section: The Effects Of Dielectric Fluids and Flowmentioning
confidence: 99%
“…They found that multi hole inner flushing bunched electrode suffers much greater peak current and results in higher MRR and high. Manish Vishwakarma et al (2012) were carried out [11] investigation study to determine the process optimal factors viz. pulse on time, input current, duty cycle gap voltage, flushing pressure for machining AISI 4140 grade steel alloy rectangular plates on output responses through RSM using the technique of DOE, ANOVA based on the CCD.…”
Section: IIImentioning
confidence: 99%